COGNITIVE ANALYSIS OF AVIATION TERMS ACROSS LANGUAGES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This thesis discusses how aviation terms are understood across different languages from a cognitive perspective. The study focuses on how people use their background knowledge, experience, and thinking processes to understand aviation vocabulary. It also looks at how differences between languages can influence the way these terms are interpreted. In some cases, direct translation does not give the exact meaning, which may lead to misunderstanding. The findings show that learners understand aviation terms better when they are presented in context, such as real communication situations.